Investigation on Tilt Angle Calculation and Irradiation on Solar Panels - ., Kasirajan; ., Sivakumar; Koon Tatt, Tan; Wai Yie, Leong (International Journal of Engineering and Technology, 2019)
The optimum choice of the tilt angle for the solar panel in order to collect the maximum solar irradiation is the most challenging work. The sun is in a different place in the sky is the idea. The sun light is different in different seasons and captures more energy by adjusting the tilt angle of the panels according to the season. Solar panels should face it as squarely as is reasonably possible throughout the day. Solar panels are installed differently based on their geographic locations throughout the world. Solar radiation differs from season to season with area wise based on the latitude of earth and sun. The influence of the  tilt angle on the solar energy collection and concluded that during winter season wide change in the tilt angle. The factors affecting the optimum tilt and azimuth angles are the regional composite feature of the solar radiation, validating the importance of the regional optimization design in improving the solar energy collection. The radiation has been calculated by calculating various factors. By setting the latitude to the location and then change the tilted surface for different seasons of the year to absorb the  solar power received.